The Characterisation of the Craniofacial Morphology of Infants Born With Zika Virus; Innovative Approach for Public Health Surveillance and Broad Clinical Applications - Ayoub, Ashraf; de Freitas Silva, Leonardo; Mossey, Peter; Al-Rudainy, Dhelal; de Mattos, Adriana Marques; Garcia Júnior, Idelmo Rangel; Quigley, Alan; Ju, Xiangyang (Frontiers in Medicine, 2021)
Background: This study was carried out in response to the Zika virus epidemic which constituted a public health emergency and to the 2019 WHO calling for strengthened surveillance for the early detection of related microcephaly. The main aim of the study was to phenotype the craniofacial morphology of microcephaly using novel approach and new measurements, relate the characteristics to brain abnormalities in Zika infected infants in Brazil to improve clinical surveillance. Methods: We captured 3D images of the face and the cranial vault of 44 Zika infected infants and matched healthy controls using 3D camera. The CT scans of the brain of the infected infants were analysed. The Principal Component Analysis (PCA) was applied to characterise the craniofacial morphology. In addition to the head circumference (HC), we introduced a new measurement, head height (HH) to measure the cranial vault. The level of brain abnormality present in the CT scans was assessed, the severity of parenchymal volume loss and ventriculomegaly was quantified. Findings: The PCA identified a significant difference (p <0.001) between the cranial vaults and the face of the Zika infants and that of the controls. Spearman's rank-order correlation coefficients show that the head height (HH) has a strong correlation (0.87 in Zika infants; 0.82 in Controls) with the morphology of the cranial vaults which are higher than the correlation with the routinely used head circumference (HC). Also, the head height (HH) has a moderate negative correlation (-0.48) with the brain abnormalities of parenchymal volume loss. Interpretation: We discovered that head height (HH), the most sensitive and discriminatory measure of the severity of cranial deformity which should be used for clinical surveillance of Zika syndrome, evaluation of other craniofacial syndromes and assessment of various treatment modalities.